Comparison of the Personality Traits of Male and Female BASE Jumpers - Monasterio, Erik; Mei-Dan, Omer; Hackney, Anthony C.; Cloninger, Robert (Frontiers in Psychology, 2018)
BASE jumping is an extreme adventure sport which consists of jumping from a fixed object with specially adapted parachutes. A few studies of the personality of BASE jumpers have been conducted, but little is known about how the women in this sport compare to the men. The purpose of this study is to compare the personality traits among a sample of men and women who are experienced BASE jumpers, as this provides an interesting and important opportunity to better understand the motivation for extreme sports. Eighty-three participants completed the Temperament and Character Inventory (TCI) the day before the jump at the New River Gorge Bridge Day BASE Jumping event, West Virginia, USA. The sample included 64 men and 19 women. Results show that men and women BASE jumpers shared similar personality traits both in terms of temperament and character, except for the character trait of cooperativeness on which women scored higher than men. This suggests that the basic drive for participation in extreme sports is self-regulation of personal emotional drives and needs for self-actualization, rather than to oppose social pressure or cultural bias against female participation. These findings are discussed in relation with other studies conducted among extreme athletes and in terms of congruence between personality and activity.